Performance of on-site Medical waste disinfection equipment in hospitals of Tabriz, Iran - Hassan Taghipour; Mina Alizadeh; Reza Dehghanzadeh; Mohammad Reza Farshchian; Mohammad Ganbari; Mohammad Shakerkhatibi (Tabriz University of Medical Sciences, 2016)
Background: The number of studies available on the performance of on-site medical waste treatment facilities is rare, to date. The aim of this study was to evaluate the performance of onsite medical waste treatment equipment in hospitals of Tabriz, Iran. Methods: A various range of the on-site medical waste disinfection equipment (autoclave, chemical disinfection, hydroclave, and dry thermal treatment) was considered to select 10 out of 22 hospitals in Tabriz to be included in the survey. The apparatus were monitored mechanically, chemically, and biologically for a six months period in all of the selected hospitals. Results: The results of the chemical monitoring (Bowie-Dick tests) indicated that 38.9% of the inspected autoclaves had operational problems in pre-vacuum, air leaks, inadequate steam penetration into the waste, and/or vacuum pump. The biological indicators revealed that about 55.55% of the samples were positive. The most of applied devices were not suitable for treating anatomical, pharmaceutical, cytotoxic, and chemical waste. Conclusion: Although on-site medical waste treating facilities have been installed in all the hospitals, the most of infectious-hazardous medical waste generated in the hospitals were deposited into a municipal solid waste landfill, without enough disinfection. The responsible authorities should stringently inspect and evaluate the operation of on-site medical waste treating equipment. An advanced off-site central facility with multi-treatment and disinfection equipment and enough capacity is recommended as an alternative.